Comparison of the Effects of LISS (Low-Intensity Steady State) and HIIT (High-Intensity Interval Training) on Cardiovascular Adaptation - Fatoni, Fatoni (Fakultas Kedokteran Universitas Sriwijaya, 2025)
Introduction. Aerobic exercise plays an important role in improving cardiovascular fitness, but each training method has different effectiveness. This study aims to compare the effects of Low-Intensity Steady State (LISS) and High-Intensity Interval Training (HIIT) on cardiovascular adaptation in students from the Department of Physical Education, Health, and Recreation, Universitas Negeri Makassar (UNM). Methods. This study used an experimental method with a pre-test and post-test control group design. A total of 54 students were divided into two groups. The first group underwent LISS training with an intensity of 50-60% of maximum heart rate (HRmax) for 40 minutes per session, while the second group underwent HIIT with an intensity interval of 85-95% HRmax for 20 minutes per session, each performed 4 times per week for 6 weeks. The cardiovascular parameters measured included VO₂ max, resting heart rate, and systolic and diastolic blood pressure. Results. The results showed that both training methods provided a significant increase in VO₂ max and a decrease in resting heart rate (p < 0.05). However, the HIIT group experienced a greater increase in VO₂ max compared to the LISS group (p < 0.05), while the LISS and HIIT pressure reduction variables were significantly able to reduce systolic and diastolic blood pressure, indicating similar benefits in terms of blood pressure control. Conclusion. The conclusion of this study is that HIIT is more effective in increasing cardiovascular adaptation, more effective in heart performance or decreasing heart rate and both are effective in reducing systolic and diastolic blood pressure.